Ethnobotany of wild and semi-wild edible plants of the Madurese Tribe in Sampang and Pamekasan Districts, Indonesia - THOBIB HASAN AL YAMINI; NINA RATNA DJUITA; TATIK CHIKMAWATI; YOHANES PURWANTO (Society for Indonesian Biodiversity, 2023)
Abstract. Al Yamini TH, Djuita NR, Chikmawati T, Purwanto Y. 2023. Ethnobotany of wild and semi-wild edible plants of the Madurese Tribe in Sampang and Pamekasan Districts, Indonesia. Biodiversitas 24: 947-957. This study aimed to inventory, identify, and characterize the diversity of wild and semi-wild edible plants (WSEPs) utilization; analyze and determine the highest importance of WSEPs based on socio-cultural, economic, and ecology; and analyze the sustainable management of WSEPs. This study was carried out in Sampang and Pamekasan Districts. The qualitative data collection was obtained by open, semi-structured, and structured interviews, while quantitative data were assessed using the pebble distribution method (PDM). Data were analyzed using the Index of Cultural Significance (ICS), Use Values ??(UVs), Local User's Value Index (LUVI), economic valuation, and important value index (IVI). The Madurese utilized 122 plant species belonging to 47 families of WSEP. The Madurese in Pamekasan District used more plant species (90 species of 30 families) than Sampang District (84 species of 20 families). These plant species were used as sources of carbohydrates, fruits, vegetables, seeds, spices, and beverages. The dominant plant families used are Anacardiaceae, Fabaceae, and Myrtaceae. Accem (Tamarindus indica) is the species with the highest ICS, UV, and LUVI values in both districts. Accem and tarebung (Borassus flabellifer) had the highest economic value. These plant species are also suggested to be maintained their species availability in their habitat.